Effect of two-body and three-body microcontacts under dry friction on contact characteristics. (February 2018) - Wu, Horng-Wen; Chen, Yang-Yuan
The wear debris generation is unavoidable between the contact interfaces of moving components. In three-body contact instances, friction and wear occur at these separate contact points. This paper discusses the characteristics of the three-body contact comprising the abrasive particle in the interface compared to the two-body contact. The results show that for the wear debris or foreign particles present in the interface of the three-body contact, as external load initially increases, the external load is fully borne by the contact characteristics of particle-to-surface. Until the external load rises to a particular critical external load, it enters the real three-body situation, and the critical external load thus increases with an increase in the ratio of particle diameter to surface roughness. For two contact surfaces, the summit deformation is the elastoplastic deformation in a wide range of external loads. As the external load is lower than the critical external load value of the three-body contact, the contact surface is under the particle-to-surface two-body contact, and the elastic deformation of surface peak has the largest proportion of contact area. When the external load is higher than the critical external load value, the elastoplastic deformation contact area quickly dominates, and the total contact area ratio approximates to the surface-to-surface two-body contact situation. In the range of engineering surface roughness (σ = 50–400 nm), at each external load and surface roughness, the total friction coefficient decreases with the increase in the ratio of particle diameter to surface roughness under the three-body contact, and this shows that the friction coefficient of surface-to-surface contact is larger than that of the sphere wear debris between the contact interface. At the same surface roughness, the friction coefficient may increase or decrease with an increase in the external load because it is determined by particle diameter. At the same ratio of particle diameter to surface roughness and external load, the friction coefficient increases with the decreasing surface roughness.